EFFICACY TEST OF TWO HERBICIDES IN CONTROL WEEDS IN SIMPLE LAND PROCESSING - Sari Sembiring, Desi Sri Pasca; Sebayang, Nico Syahputra (Jurnal Pertanian, 2019)
Residents of agrarian areas are residents who depend their livelihood to agricultural products, but the production of community plantations is often not as desired. Our research aims to know  influence the physiological response of weeds to glyphosate herbicide and paraquat herbicide. This experiment was conducted at the UGL Kutacane Faculty of Agriculture experimental garden, Babussalam Subdistrict, Southeast Aceh Regency, which ran from January to February 2018. This study used a non-factorial Randomized Block Design (RBD) consisting of 4 treatment levels: H1: Glyphosate Herbicide = 300 ml/4 L water; H2: Glyphosate herbicide = 1000 ml/13 L water; H3: Herbicide Paraquat = 300 ml/4 L water; H4: Herbicide Paraquat = 1000 ml/13 L of water. The results of Glyphosate Herbicide 1000 ml / 13 L of water effectively control total weeds up to 14 HSA. Glyphosate herbicide is able to inhibit the 5-enolpiruvil-shikimat-3-phosphate synthase (EPSPS) enzyme which plays a role in the formation of aromatic amino acids. The author concludes that the recommended dose of glyphosate based on the research is 1000 ml/13 L of water, because the dose is herbicide Glyphosate has been able to suppress total weed growth.